Data from: Survey of haemosporidian parasites in resident and migrant game birds of Illinois - Annetti, Kendall L.; Rivera, Nelda A.; Andrews, John E.; Mateus-Pinilla, Nohra (Dryad, 2017)
Haemosporidian parasites are globally distributed in avian species, capable of leading to decreased reproductive success, weakness and mortality. Haemosporidian parasites that affect reproduction and population growth are of interest to bird conservation groups and to organizations concerned with the health and immunological status of avian populations. Haemosporidian infection data are not always available for some avian species in specific regions yet. These data provides the starting points to evaluate geographical and temporal changes in the patterns of infection and prevalence across populations. We examined haemoparasite infections in four game bird species commonly hunted in Illinois. Prevalence, mean intensity, median intensity and mean abundance of haemosporidians were calculated, and the relation of these infection measures associated with age and sex of the avian hosts were evaluated. Game species sampled (n = 237) included migrants such as mourning doves (Zenaida macroura), wood ducks (Aix sponsa) and Canada geese (Branta canadensis), as well as resident birds such as wild turkeys (Meleagris gallopavo). Only Haemoproteus, Plasmodium, and Leucocytozoon species were identified. Haemoproteus was the most prevalent haemosporidian (46/237), followed by Plasmodium (11/237). Furthermore, Haemoproteus was the most persistent haemosporidian, as it was the only parasite genera found in all four avian species. Co-infections were found in 55% of turkeys, but no significant correlations between the genera of haemosporidinan co-infections and a host species were found. Moreover, no significant differences in the proportion of infected individuals (prevalence) and haemosporidian quantities (levels of intensity and abundance) were related to biotic factors such as age and sex of the host. However, parasite aggregation (distribution of parasites among hosts) was affected by age, as adult turkeys and juvenile doves showed the highest aggregation index (Poulin’s index of discrepancy D) for Haemoproteus spp. This study ...